(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Endometrial hyperplasia represents a heterogeneous group of lesions with variable potential for progression to endometrial carcinoma. The tumor suppressor gene PTEN plays a critical role in endometrial carcinogenesis, and its altered expression has been identified as an early molecular event. Aim: To evaluate the immunohistochemical expression of PTEN in endometrial hyperplasias and compare it with endometrial carcinomas. Materials and Methods: This prospective observational study was conducted in the Department of Pathology in collaboration with the Department of General Surgery over a period of nine months (June 2025 to February 2026). A total of 132 endometrial samples were studied, including 100 cases of endometrial hyperplasia (88 without atypia and 12 with atypia), 14 cases of endometrial carcinoma, and 18 normal endometrial samples serving as controls. Histopathological evaluation was performed using hematoxylin and eosin staining. Immunohistochemical analysis for PTEN expression was carried out using monoclonal antibody (clone 28H6). PTEN expression was assessed based on the percentage of positive glands, staining intensity, stromal expression, and presence of null glands. Results: Endometrial hyperplasia without atypia showed the highest PTEN expression, with 75% of cases demonstrating >50% positive glands and predominantly moderate to strong intensity. In contrast, hyperplasia with atypia showed reduced expression, with 50% of cases exhibiting <10% positive glands and weaker staining intensity. Endometrial carcinomas demonstrated markedly reduced or absent PTEN expression, with 57.1% of cases showing <10% glandular positivity and predominantly weak or absent staining. Stromal PTEN expression decreased progressively from hyperplasia without atypia to carcinoma. Null gland number and clustering increased significantly across the spectrum. The differences in PTEN staining intensity (p = 0.012) and null gland distribution (p = 0.000) between hyperplasia without atypia and atypical hyperplasia were statistically significant. Conclusion: PTEN expression decreases progressively from benign to malignant endometrial lesions, highlighting its role in endometrial tumorigenesis. Immunohistochemical assessment of PTEN is a valuable adjunct in differentiating endometrial hyperplasias and carcinomas and may aid in early detection and risk stratification.